Determination of the Migration of Lactide in PLA Food Contact Materials by Gas Chromatography Mass Spectrometry - Ying ZENG; Yanfen CHEN; Ming ZENG; Sheng CHEN; Jingjing PAN; Dan LI; Huaining ZHONG; Ben DONG; Jianguo ZHENG (Shipin gongye ke-ji, 2023)
The method for the determination of migration of lactide in polylactic acid (PLA) food contact material by gas chromatography-mass spectrometry (GC-MS) was established. Olive oil simulants were extracted by acetonitrile, centrifuged and filtered, and then analyzed by GC-MS. Isooctane simulants were directly filtered and analyzed by GC-MS. The method could achieve the determination of lactide migration in PLA. The limit of detection was 0.01 mg/kg and the recoveries at spiked levels were 80.0%~120.0%. The relative standard deviations were 2.6%~6.6% (n=6). Seven PLA samples were analyzed by the method. The detection rate was 85.7% and the range of concentration were 0.033~1.1 mg/kg. The method had the advantages of high sensitivity, high recovery and accuracy. The detection limit can meet the requirements of regulations. The method was suitable for migration of lactide in PLA food contact materials. The results showed that the detection rate of migration of lactide in PLA samples was high and migration of lactide should be paid attention to. Compared with isooctane, the migration of olive oil in the sample was higher than that of isooctane under the substitution condition due to the higher migration temperature of olive oil.